The Influence of Store Atmosphere and Consumer Emotion on Purchasing Decisions at Blackcup Coffee and Roastery Manado - Erdiansyah Wuniarto; Paulus Kindangen; Merinda H.C. Pandowo (Universitas Sam Ratulangi, 2022)
This study will analyze the effect of store atmosphere and customer emotions on purchasing decisions at Black Cup Coffee and Roastery Manado. The formulation of the problem in this study is whether there is an influence between store atmosphere and customer emotions on purchasing decisions. This research is a field research with a quantitative research model. The type of data used in this study is primary data collected using a questionnaire given to 100 customers of Black Cup Coffee and Roastery Manado. The analysis used in this study is the classical assumption test and multiple regression analysis. The results of this study indicate that there is a negative and not significant effect of store atmosphere on purchasing decisions at Black Cup Coffee and Roastery with a t value of -0.517. On the significant influence between customer emotions on purchasing decisions at Black Cup Coffee and Roastery with a t value of 5.628. Simultaneously store atmosphere and emotions have a significant effect on purchasing decisions with a calculated f value of 21,092, which affects store atmosphere and customer emotions affect purchasing decisions at Black Cup Coffee and Roastery Manado.